From historical foundations to contemporary structures: Tracing Qatar’s mental health services from the 1950s to 2025 - Maha AlMuraikhi (22986631) (2025)
Qatar’s mental health (MH) system has expanded rapidly since the 1950s alongside economic growth, urbanization, and major demographic change. This narrative review traces service development from the first psychiatric unit at Rumailah Hospital (1957) to contemporary structures spanning Hamad Medical Corporation, the Primary Health Care Corporation, Sidra Medicine, and Naufar. We describe how sociocultural factors, workforce and education reforms, and legislation, including the National MH Strategy (2013–2018) and MH Law (2016), shaped provision, with attention to migrant populations, women, and children. We also summarize integration efforts (e.g., PHCC stepped-care, telepsychiatry, and the national helpline) and persistent gaps (limited community rehabilitation, child inpatient capacity, and uneven access). Drawing on international benchmarks, we outline options that may strengthen community-based care, psychological therapies, and legal implementation, recognizing the descriptive nature of the available evidence. This descriptive account contextualizes current challenges and recent gains to inform planning for an inclusive, sustainable MH system. Other Information Published in: Asian Journal of Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajp.2025.104765